Threat captures attention, but not automatically: Top-down goals modulate attentional orienting to threat distractors - Vromen, J.; Lipp, Ottmar; Remington, R.; Becker, S. (Springer, 2016)
The rapid orienting of attention to potential threats has been proposed to proceed outside of top-down control. However, paradigms that have been used to investigate this have struggled to separate the rapid orienting of attention (i.e. capture) from the later disengagement of focal attention that may be subject to top-down control. Consequently, it remains unclear whether and to what extent orienting to threat is contingent on top-down goals. The current study manipulated the goal-relevance of threat distractors (spiders), whilst a strict top-down attentional set was encouraged by presenting the saliently colored target and the threat distracter simultaneously for a limited time. The goal-relevance of threatening distractors was manipulated by including a spider amongst the possible target stimuli (Experiment 1: spider/cat targets) or excluding it (Experiment 2: bird/fish targets). Orienting and disengagement were disentangled by cueing attention away from or towards the threat prior to its onset. The results indicated that the threatening spider distractors elicited rapid orienting of attention when spiders were potentially goal-relevant (Experiment 1) but did so much less when they were irrelevant to the task goal (Experiment 2). Delayed disengagement from the threat distractors was even more strongly contingent on the task goal and occurred only when a spider was a possible target. These results highlight the role of top-down goals in attentional orienting to and disengagement from threat. © 2016 The Psychonomic Society, Inc.